Max Planck School of Photonics: Research-oriented photonics education in a network of excellence throughout Germany - Geiss, Reinhard; Hengster, Julia; Kaiser, Thomas; Leuchs, Gerd; Tuennermann, Andreas (Optics InfoBase Conference Papers, 2019)
The Max Planck School of Photonics (MPSP) provides and coordinates an integrated program for the photonics education of graduate and doctoral students in a network of excellence of German universities and research institutions. Students can choose to start the program with a qualification phase to obtain a photonics Master's degree from one of three teaching universities in Erlangen, Jena or Karlsruhe. The subsequent PhD-phase lasts three years and the research work is conducted under the supervision of one out of 45 Fellows of the MPSP. Students already holding a qualifying Master's degree can apply to directly enter the PhD-phase of the program. Apart from an excellent network of renowned scientists and research institutions, the MPSP offers generous financial support and a supporting curriculum to foster interactions between the different photonics disciplines, to strengthen the research network and to advance personal and professional skills. Maintaining and supporting active interactions of the MPSP research network at all levels is challenging and will be backed up by employing digital learning tools and platforms. Here, we will present our recent findings on chances and opportunities provided by the MPSP's educative approach.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Digital learning; Graduate school; Max Planck School of Photonics; Max Planck Schools